2020
DOI: 10.1002/jbmr.4415
|View full text |Cite
|
Sign up to set email alerts
|

Sites of Cre-recombinase activity in mouse lines targeting skeletal cells

Abstract: The Cre/Lox system is a powerful tool in the biologist's toolbox, allowing loss-of-function and gain-of-function studies, as well as lineage tracing, through gene recombination in a tissue-specific and inducible manner. Evidence indicates, however, that Cre transgenic lines have a far more nuanced and broader pattern of Cre activity than initially thought, exhibiting "off-target" activity in tissues/cells other than the ones they were originally designed to target. With the goal of facilitating the comparison … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 284 publications
(576 reference statements)
1
12
0
Order By: Relevance
“…Another plausible explanation is that the Cre-Col II system affected brain SIRT1, as effects similar to those we see in learning, memory and anxiety were previously reported in brain-specific SIRT1 knockout mice (BSKO) (22,23), this is in spite of the fact that the driver that we used for Cre was Col type II and not nestin (34). Indeed, a recent review summarized the off-target effect of many skeletal Cre lines, showing that most Cre lines show some level of unintended activity in other tissues (35), thus the notion that Cre lines are specific to a particular cell or tissue has been misleading. While collagen type II is usually considered a hallmark for chondrogenic differentiation, several publications on mouse embryogenesis (9,(15)(16)(17), as well as a study on the Cre Col II system (36) showed transient expression of Col type II mRNAs in a number of non-chondrogenic tissues such as notochord, sclerotome, pre-chondrogenic mesenchyme, heart, brain and eye.…”
Section: Discussionsupporting
confidence: 59%
“…Another plausible explanation is that the Cre-Col II system affected brain SIRT1, as effects similar to those we see in learning, memory and anxiety were previously reported in brain-specific SIRT1 knockout mice (BSKO) (22,23), this is in spite of the fact that the driver that we used for Cre was Col type II and not nestin (34). Indeed, a recent review summarized the off-target effect of many skeletal Cre lines, showing that most Cre lines show some level of unintended activity in other tissues (35), thus the notion that Cre lines are specific to a particular cell or tissue has been misleading. While collagen type II is usually considered a hallmark for chondrogenic differentiation, several publications on mouse embryogenesis (9,(15)(16)(17), as well as a study on the Cre Col II system (36) showed transient expression of Col type II mRNAs in a number of non-chondrogenic tissues such as notochord, sclerotome, pre-chondrogenic mesenchyme, heart, brain and eye.…”
Section: Discussionsupporting
confidence: 59%
“…To further explore potential effects on osteoclast differentiation, ex vivo osteoclastogenesis assays were performed. Bone marrow macrophages were collected from Phlpp1 cKOLysM females and their sex-matched littermate controls and cultured in the presence of RANKL and M-CSF as previously described [13,19,20]. Diminished expres sion of Phlpp1 was confirmed of ex vivo osteoclasts derived from Phlpp1 cKOLysM mice (Figure 3A,E).…”
Section: Conditional Deletion Of Phlpp1 Enhances Osteoclastogenesismentioning
confidence: 87%
“…One option relates to the limitations arising from the currently available Cre lines that target osteoclast progenitors and may be due to (i) the heterogeneity and plasticity of osteoclast precursors, both under steady state and pathological conditions [ 54 ], i.e., not all osteoclast precursors express LysM or Cx3cr1, and (ii) the limited depletion efficiency and targeting specificity in myeloid specific Cre transgenes [ 55 ]. These limitations led us to utilize two separate Cre lines, LysM Cre and Cx3cr1 Cre , with different off-target sites, in order to delete EPOR in the early osteoclast lineage [ 56 ]. Cx3cr1 Cre is relatively more specific to the monocyte/macrophage lineage than LysM Cre , although there are also effects on neutrophils, mast cells, and classical dendritic cells [ 57 ].…”
Section: Discussionmentioning
confidence: 99%